2018
DOI: 10.4103/abr.abr_99_17
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Herbal Gel of Antirrhinum majus Extract and Evaluation of its Anti- Propionibacterium acne Effects

Abstract: Background:Antirrhinum majus contains aurone with excellent antibacterial and antifungal activities. In addition, visible light activates the endogenous porphyrins of Propionibacterium acne, which results in bacterial death. Therefore, considering the above-mentioned facts, the aim of the present study was to prepare a topical herbal gel of A. majus hydroalcoholic extract and to evaluate its antiacne effects with or without blue light combination as an activator of the porphyrins.Materials and Methods:Antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…For the formulated gels, the results of the pH showed that the gel systems were within acceptable pH range. The gels showed a pH range of 6.8-7.1 and this is in accordance with Shahtalebi et al [44]. The effect of pH on skin infections have been studied and it has been observed that at low pH values of 4.7, Staphylococcus epidermidis shows growth, while Staphylococcus aureus is suppressed at a pH value of 7 [45].…”
Section: Discussionsupporting
confidence: 86%
“…For the formulated gels, the results of the pH showed that the gel systems were within acceptable pH range. The gels showed a pH range of 6.8-7.1 and this is in accordance with Shahtalebi et al [44]. The effect of pH on skin infections have been studied and it has been observed that at low pH values of 4.7, Staphylococcus epidermidis shows growth, while Staphylococcus aureus is suppressed at a pH value of 7 [45].…”
Section: Discussionsupporting
confidence: 86%
“…Gel rửa mặt được coi là kém chất lượng nếu lượng mực bị cô đặc trong bọt, các chất bẩn nên tồn tại trong phần nước vì nếu bụi bẩn còn sót lại trong phần bọt sẽ rất khó tẩy rửa và sẽ bám lại trên da, không làm sạch được da mặt. Yêu cầu không có mực trong bọt [9].…”
Section: Phương Pháp Nghiên Cứuunclassified
“…The plants samples were identified by Botanical Survey of India (BSI), Western Regional Center, Pune, Maharashtra, India. 5% gel was prepared from aqueous fractions of Ficus religiosa L. and Morus Alba L. in combination according to modified protocol based on procedure described previously 33 . Briefly, the individual fractions were dissolved in 4 ml of distilled water followed by addition of 4% propylene glycol and 3% ethanol.…”
Section: Plants Samples Collection and Formulationmentioning
confidence: 99%